KNOWLEDGE AND ATTITUDES OF SCHOOL-AGE CHILDREN TOWARDS VEGETABLE AND FRUIT CONSUMPTION AT SD NEGERI 9 PEKANBARU - Mustikawati Mustikawati; Wd Erty Hikma (International Journal of Health Science & Medical Research, 2022)
There are more cases of malnutrition than other cases, such as stunted growth of children and loss of vitamins and minerals. Lack of consumption of vegetables and fruit causes children to be susceptible to malnutrition. The novelty of this study is because it examines the knowledge and attitudes of school-age children towards vegetable and fruit consumption at SD Negeri 9 pekanbaru The purpose of this study was to determine the relationship between knowledge and attitudes towards vegetable consumption in school-age children. This research is a quantitative type of research using cross sectional method which was conducted in July 2015 to determine the knowledge and attitude scores. This research was conducted at the State Elementary School 9 Pekanbaru in a school environment where school children are easier to lack nutrients such as vitamins and minerals during their growth period. Of the 88 respondents studied, there is a significant relationship between knowledge of consumption of vegetables and fruit indicated by a P Value of 0.008 0.05 (OR: 4.667. CI: 1.570 – 13.874). For attitudes, there is a relationship between attitudes towards consumption of vegetables and fruit in school children. P value 0.004 0.05 (OR : 6.500, CI : 2.049 – 20.619) From the results of this study, consumption of vegetables and fruit in children is still lacking. Consumption of vegetables and fruit can be increased through the role of parents and teachers in schools so as to reduce the problem of malnutrition. In addition, facilities and infrastructure in schools can also support children to be able to consume enough vegetables and fruit every day.Keywords: Knowledge and attitudes of school-age children; consumption of vegetables and fruit for school-age children.